Aloe Emodin Reduces Cardiac Inflammation Induced by a High-Fat Diet through the TLR4 Signaling Pathway - Yingfu Chen; Burong Feng; Ye Yuan; Juan Hu; Wei Zhao; Huiwei Jiang; Wen Li; Ziyi Fan; Zhimin Du (Mediators of Inflammation)
Background. Aloe emodin (AE) is a lipid-lowering agent, which could be used to treat hyperlipidemia, thereby reducing the risk of cardiovascular disease. Recent evidence suggests that hyperlipidemia is associated with many cardiac pathological alterations and might worsen myocardial damages. Purpose. The purpose of this study is to evaluate the potential roles and mechanisms of AE in hyperlipidemia-induced oxidative stress and inflammation in the heart. Study Design. We established a hyperlipidemia-induced cardiac inflammation model in rats and cells then administered AE and observed its effect on hyperlipidemia-induced cardiac inflammation. Methods. We used a mouse model of hyperlipidemia caused by a high-fat diet (HFD) for 10 weeks and cell culture experimental models of inflammation in the heart stimulated by PA for 14 h. Inflammatory markers were detected by qRT-PCR, WB, and immunofluorescence. Results. We demonstrated that the expression levels of proinflammatory cytokines IL-1β, IL-6, and TNF-α were increased in the HFD group compared to the normal diet (ND) group, whereas AE treatment significantly reduced their levels in the myocardium. In addition, vascular cell adhesion molecule 1 (VCAM1) and intercellular adhesion molecule 1 (ICAM-1) protein expressions were also inhibited by AE. Our in vitro study showed AE treatment dose-dependently decreased the expression of IL-1β, IL-6, and TNF-α in PA-treated H9C2 cells. Further experiments revealed that AE inhibited PA-induced cell death and promoted the production of intracellular reactive oxygen species (ROS). Mechanically, AE significantly suppressed the upregulation in protein levels of TLR4, IκB, and p-P65l in vivo and in vitro. Conclusion. Taken together, our findings disclose that AE could alleviate HFD/PA-induced cardiac inflammation via inhibition of the TLR4/NF-κB signaling pathway. Thus, AE may be a promising therapeutic strategy for preventing hyperlipidemia-induced myocardial injury.